Seed‐Mediated Growth of Colloidal Metal Nanocrystals. Issue 1 (14th December 2016) - Xia, Younan; Gilroy, Kyle D.; Peng, Hsin‐Chieh; Xia, Xiaohu
Abstract: Seed‐mediated growth is a powerful and versatile approach for the synthesis of colloidal metal nanocrystals. The vast allure of this approach mainly stems from the staggering degree of control one can achieve over the size, shape, composition, and structure of nanocrystals. These parameters not only control the properties of nanocrystals but also determine their relevance to, and performance in, various applications. The ingenuity and artistry inherent to seed‐mediated growth offer extensive promise, enhancing a number of existing applications and opening the door to new developments. This Review demonstrates how the diversity of metal nanocrystals can be expanded with endless opportunities by using seeds with well‐defined and controllable internal structures in conjunction with a proper combination of capping agent and reduction kinetics. New capabilities and future directions are also highlighted. Abstract : Grown from seed : Metal nanocrystals are essential to many applications in science and technology. Of all the synthetic procedures, seed‐mediated growth offers unrivalled control to produce colloidal metal nanocrystals with well‐defined sizes, shapes, structures, and compositions.